Vegetarianism - Francis, Amy. (Farmington Hills, Mich. : Greenhaven Press, a part of Gale, Cengage Learning, 2015)
This collection of articles pro and con on vegetarianism examines whether meat-based diets are bad for the planet, the moral and spiritual implications of vegetarianism, the extent to which vegetarian diets are more humane that diets that include meat, and whether a vegetarian diet is beneficial for health.
Overview: People choose their diets based on personal reasons / Stephanie Kraftson, Jana Pohorelsky, and Alex Myong -- Vegetarians contribute to global food security / Live58 -- Meat-based diets perpetuate global hunger and climate change / Mimi Bekhechi -- Livestock contributes to global warming / Robert Goodland and Jeff Anhang -- Meat production can benefit the earth / Doug Boucher et al. -- Cattle can be used to reverse global warming / Adam D. Sacks -- Grazing animals improve soil quality / Heather Dugmore -- Plant-based diets' environmental impact examined in French study / Andrew Seaman -- Overview: Vegetarians' beliefs are just as sincere as those of traditional religious faiths / Sherry F. Colb -- Vegetarianism is a moral decision with many benefits / Melanie Joy -- Vegetarianism is the only morally acceptable diet / Robert Grillo -- Buddhists are permitted to consume meat / Wayne Hughes -- There are spiritual benefits to vegetarianism / George Burke -- There is a moral middle ground in the omnivore vs. vegetarian debate / Joe Perez -- Overview: The evolution of vegetarianism / Sari Kamin -- Pro-animal, pro-life / Mary Eberstadt -- Vegetables can be grown without the use of animal products / John Walker -- Animals suffer needlessly for food production / Ted Genoways -- Vegetarians may be responsible for more animal deaths than omnivores / Julie Galef -- Vegetarian diets cause more animal cruelty than eating meat / Mike Archer -- Even small-scale vegetable farming requires hunting animals / Tovar Cerulli -- Vegan diets are good for athletes / Scott Jurek -- A plant-based diet has impressive benefits / Sharon Palmer -- Meat-based diets improved human intelligence / Christopher Joyce -- Not everyone benefits from a vegetarian diet / Sandro D'Amico -- Vegetables cause more cases of food poisoning than meat / NHS Choices -- Vegetarian diets are not healthy / Kris Gunnars.
Includes bibliographical references (pages 210-214)) and index.
Keywords: Vegetarianism -- Juvenile literature; Diet -- Moral and ethical aspects -- Juvenile literature; Meat industry and trade -- Moral and ethical aspects -- Juvenile literature; Food preferences -- Juvenile literature; Meat industry -- Ethical aspects; Eating customs; Vegetarianism; Diet -- Moral and ethical aspects; Meat industry and trade -- Moral and ethical aspects; Vegetarianism; Food preferences; Diet -- Ethical aspects; Diet -- Moral and ethical aspects; Food preferences; Vegetarianism; Literature; Juvenile works; Literature